Studying the Physical Properties of Silver Telluride Films Doped with Aluminum by the Effect of Annealing - liqaa Al-Dulaimi; Aliyah A. Shihab (Ibn Al-Haitham Journal for Pure and Applied Sciences)
The structural and optical properties of silver telluride films with doped 2% aluminum (Ag2Te:2%Al), prepared using the thermal evaporation technique, were studied on glass substrates with a thickness of (400+ 20) nm after changing the annealing temperature to (300° C) for one hour. The films were found to be polycrystalline, and monoclinic at room temperature (R.T.), the structure became cubic after annealing. In XRD test we found that the crystallite size of the doped films is larger before annealing than it is for the (Ag2Te:2%Al) films, and AFM tests showed that the grain size increases after annealing It also shows that the structure is nano, UV-visible optical tests of Ag2Te films revealed that absorbance values decrease after annealing while the absorption coefficient increases, ascertain the values of the absorption coefficient depending on the equation that links the values of the absorption coefficient with absorbance [α=  (2.303)A/t]. The energy gap for pure films reduces after doping and annealing. The optical absorption coefficient (α) value for each film was greater than (104 cm -1) this means all films have an optical energy gap with direct transmission.